Pola Rekruitmen Politik Partai Nasdem Kota Makassar Menuju Pemilihan Legislatif Tahun 2024 - Muh Amril Pratama Putra; Hasan Rahman; Muhammadiah Muhammadiah (Universitas Muhammadiyah Makassar, 2022)
This study aims to describe and explain the Implementation of Political Party Functions in the Recruitment of National Democratic Party Cadre (NAsDEM) Makassar City to get votes in the 2024 election, as well as widening the number of members with a recruitment mechanism that can be used as a mass basis of votes in facing the 2024 election. This type of research is using qualitative methods to describe and explain the Implementation of Political Party Functions as Recruitment for Cadre of the National Democratic Party (NAsDEM) Makassar City. Data collection techniques using the method of observation, interviews and documentation. Data analysis using interactive model. The results showed that the Implementation of the Functions of Political Parties as Recruitment for Cadre of the National Democratic Party (NAsDEM) Makassar City, that the NasDem Party had an open recruitment pattern and a closed recruitment pattern.